When the Threat Is Stronger Than the Execution: Trade and Welfare under Oligopoly - Dermot Leahy; J. Peter Neary (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We compare trade liberalization under Cournot and Bertrand competition in reciprocal markets. In both cases, the critical level of trade costs below which the possibility of trade affects the domestic firm's behavior is the same; trade liberalization increases trade volume monotonically; and welfare is U-shaped under reasonable conditions. However, welfare is typically greater under Bertrand competition; for higher trade costs the volume of trade is greater under Cournot competition, implying a “van-der-Rohe Region” in parameter space; and, for even higher trade costs, there exists a “Nimzowitsch Region”, where welfare is higher under Bertrand competition even though no trade takes place.
Keywords: L13; F12; 330; Cournot and Bertrand Competition; Nimzowitsch Region; oligopoly and trade; trade liberalization; van-der-Rohe Region